Transformasi Spiritual dari Penderitaan Menuju Kemuliaan dalam Perspektif Yesaya 50:4-11 - Limbong, Sukanto (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
This research explores the complex dialectic between suffering and glory in the spiritual context depicted in Isaiah 50:4-11, focusing on the transformation of the calling of God's servant. Through a hermeneutical analysis, this study reveals how the experience of suffering serves as a fundamental medium for the formation of spiritual character and the growth of faith. The findings indicate that suffering in the context of Isaiah 50:4-11 is not merely a negative experience but a dialogical space in which God shapes the identity and mission of His servant. The conclusion emphasizes that faithfulness to God is manifested not through the avoidance of suffering, but through an attitude of obedience and surrender that allows for profound spiritual transformation.